Effect of Spraying Eucalyptus extraction and VitaminC and acetylsalicylic acid on some growth characteristics and yield of the plant vicia faba L. (Journal of the College of Basic Education, 2022)
An experiment was conducted to assess the effect of Eucalyptus extraction and VitaminC and acetylsalicylic acid on some vegetative growth characteristics and yield content of bean plant (Vicia faba L.). The experiment was carried out in the botanical garden of college of Education Ibn-ALhaitham,University of Baghdad during the growing season2010-2011. Result indicated that the concentrations5%,10%of Eucalyptus extraction gave significantly effect that increase the crop growth speed ,relative growth rate of the leaves,No. of pods /plan ,length of pod,No.of grains /pod percentage of the soluble carbohydrate in the grains,and percertage of protein in the grains .on the other hand the concentration 40ppmVitaminC increased the thickness of the stem (mm),while the concentration 20ppm Vitamin C gave on increasing in the leaf area index .The two concentrations (40,60)ppm of acetylsalicylic acidgave on increasing in stem length ,no of pods ,weight of grain.